Management - Robbins, Stephen P.; Coulter, Mary K. (Pearson, 2021)
This title is a Pearson Global Edition. The Editorial team at Pearson has worked closely with educators around the world to include content which is especially relevant to students outside the United States. For management and non-management majors taking an undergraduate course in the principles of management. REAL managers, REAL experiences. With a renewed focus on job-relevant skills, the newest edition of this bestselling text helps management and non-management students alike better prepare to enter the workforce. Management, 15th Edition, Global Edition, vividly illustrates effective management theories by incorporating the perspectives of real-life managers. Through examples, cases, and hands-on exercises, students will see and experience management in action-helping them develop the specific skills that employers are looking for and understand how the concepts they're learning about actually work in today's dynamic business world. Pearson MyLab Management is not included. Students, if Pearson MyLab Management is a recommended/mandatory component of the course, please ask your instructor for the correct ISBN. Pearson MyLab Management should only be purchased when required by an instructor. Instructors, contact your Pearson representative for more information. Reach every student by pairing this text with Pearson MyLab Management. MyLab (TM) is the teaching and learning platform that empowers you to reach every student. By combining trusted author content with digital tools and a flexible platform, MyLab personalizes the learning experience and improves results for each student.